2013
DOI: 10.1016/j.sedgeo.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Paleocurrent direction measurements in a volcanic setting by means of anisotropy of magnetic susceptibility: A case study from the Lower Miocene Tepoztlán Formation (Transmexican Volcanic Belt, Central Mexico)

Abstract: Sources of ancient volcanic rocks are often unknown if they are either eroded and/or covered by younger deposits. This problem, as well as the provenance of reworked volcaniclastic, fluvial and mass-flow deposits, can be partially solved by the application of anisotropy of the magnetic susceptibility (AMS). For massive and poorly sorted volcaniclastic rocks in particular this may be the only way of finding reliable transport directions and therefore allowing for paleogeographic reconstructions. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…Samples with extreme Pj values are characterized by anomalously high magnetic susceptibility (Km), which indicates the contribution of strongly magnetic lithic fragments in such samples. The role of abundant lithoclasts in weakening the magnetic fabric in volcanogenic mass-flow deposits is supported by the results of Lenhardt et al (2013) who showed the weakening of magnetic fabric in volcanogenic sedimentary sequences (conglomerates) with increasing grain size. Conglomerates show weaker fabrics than those found in PDC deposits with fine-grained matrix and in volcanogenic sandstones.…”
Section: Comparison Between Fabric Strength Of a Subaqueously Emplacementioning
confidence: 71%
See 1 more Smart Citation
“…Samples with extreme Pj values are characterized by anomalously high magnetic susceptibility (Km), which indicates the contribution of strongly magnetic lithic fragments in such samples. The role of abundant lithoclasts in weakening the magnetic fabric in volcanogenic mass-flow deposits is supported by the results of Lenhardt et al (2013) who showed the weakening of magnetic fabric in volcanogenic sedimentary sequences (conglomerates) with increasing grain size. Conglomerates show weaker fabrics than those found in PDC deposits with fine-grained matrix and in volcanogenic sandstones.…”
Section: Comparison Between Fabric Strength Of a Subaqueously Emplacementioning
confidence: 71%
“…Recent studies (Capaccioni and Sarocchi 1996, Capaccioni et al, 1997, Valentini et al, 2008, Biró 2013) applied computer-assisted image analysis to determine directional fabric. Another widely used approach is the application of anisotropy of magnetic susceptibility (AMS), which gives information on the directional fabric in an indirect way by measuring the alignment of magnetic and paramagnetic minerals (e. g. Ellwood, 1982;MacDonald and Palmer, 1990;Lamarche and Frogatt, 1993;Fisher et al, 1993;Cagnoli and Tarling, 1997;Le Pennec et al, 1998;Ort et al, 2003;Porreca et al, 2003;Caballero-Miranda et al, 2009;LaBerge et al, 2009;Dedzo et al, 2011;Lenhardt et al, 2013). Studying the directional fabric in such deposits is advantageous for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy of magnetic susceptibility is a geophysical technique that has been widely used to infer depositional patterns and tectonic evolution in hard rocks (Hamilton and Rees, 1970;Rathore, 1979;Borradaile and Henry, 1997;Dragoni et al, 1997;Lüneburg et al, 1999;Li et al, 2014). This technique has also been applied to unconsolidated sediments to deduce flow direction during deposition (Rees and Woodall, 1975;Ellwood, 1980;Hassold et al, 2009;Lenhardt et al, 2013;Park et al, 2013;Wassmer et al, 2015). Here we use the abbreviation MF (Magnetic Fabric) to refer to Anisotropy of Magnetic Susceptibility, to avoid confusion with the AMS acronym applied to radiocarbon dating.…”
Section: Magnetic Fabric Measurements In Tsunami Depositsmentioning
confidence: 99%
“…In an attempt to cover the entire sedimentary succession of the Tepoztlán Formation, The sediments within the two stratigraphic sections accumulated in proximal to median environments (not more than 5 -10 km from the source area), in flank and apron settings of a volcanic ring plain (shedding its debris from north to south), interfingering with an axial W-E trending braided river system (Lenhardt et al, 2010;2011;2013). While the lower part of the San Andrés section is still predominantly characterized by sandstones and conglomerates of the axial braided river system, the influence of the volcanic ring plain increases up-section and completely dominates the Tepozteco section (ca.…”
Section: Sampling Localitiesmentioning
confidence: 99%
“…The initial volcanic activity of the early TMVB is dated to ca. 22 Ma and is documented by the Tepoztlán Formation (Lenhardt et al, 2010(Lenhardt et al, , 2013Lenhardt and Götz, 2011), cropping out in Malinalco (Mexico State) and in Tepoztlán and Tlayacapan (Morelos). The geology and geography of Morelos in Central Mexico controlled the evolution of the local flora and fauna (c.f., Lenhardt et al, 2006;Graham, 2010Graham, , 2011.…”
Section: Introductionmentioning
confidence: 99%